Association of Radiographic Soft Tissue Thickness with Revision Total Ankle Arthroplasty Following Primary Total Ankle Arthroplasty: A Minimum of 5-year Follow-up - Kevin Wu BS; Albert T. Anastasio MD; Alexandra Krez MD; Katherine Kutzer BS; James K. DeOrio MD; Mark E. Easley MD; James A. Nunley MD; Samuel B. Adams MD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: The incidence of primary total ankle arthroplasty (TAA) is rising, with a corresponding increase in revision surgeries. Despite this, research on risk factors for revision TAA following primary TAA remains limited. Radiographic soft-tissue thickness has been explored as a potential predictor for outcomes in hip, knee, and shoulder arthroplasty, but its role in TAA has not been assessed. This study aimed to assess the predictive value of radiographic soft tissue thickness for identifying patients at risk of requiring revision surgery following primary TAA. Methods: A retrospective study was conducted on 323 patients who underwent primary TAA between 2003 and 2019. Radiographic measurements of soft tissue thickness were obtained from preoperative lateral weightbearing radiographs. Clinical variables including age, gender, body mass index (BMI), American Society of Anesthesiologists (ASA) classification, diabetes, smoking status, primary diagnosis, and implant type were recorded. Logistic regression analysis was used to assess the predictive value of soft tissue thickness and BMI for revision TAA. Results: The rate of revision surgery was 4.3% (14 out of 323 patients). Patients requiring revision had significantly greater tibial-tissue (3.54 vs. 2.48 cm; p=0.02) and talus-tissue (2.79 vs. 2.42 cm; p=0.02) thickness compared to those who did not require revision. Both the Tibial-Tissue thickness (Odds Ratio: 1.16 [1.12-1.20]; p < 0.01) and the Talus-Tissue thickness (Odds Ratio: 1.10 [1.05-1.15]; p < 0.01) measurements were significant predictors of revision TAA in multivariable logistic regression models. In contrast, BMI was not a significant predictor of revision TAA. The two metrics demonstrated excellent interrater reliability. Conclusion: Greater soft tissue thickness, as measured radiographically, was a better predictor of revision TAA compared to BMI. These findings suggest that radiographic soft tissue thickness may be a valuable tool for assessing the risk of the need for revision TAA following primary TAA. Further research is needed to validate these findings and explore the potential impact on clinical practice. Figure 1. Radiographical Assessment of Tissue Thickness The figure illustrates the method for obtaining the radiographic measurements on weightbearing lateral radiographs. (A) A line was drawn from the posterior distal tibia to the anterior distal tibia (Red Line), and the distance of the parallel segment extending from the anterior cortex of the tibia to the end of the soft tissue shadow was measured to determine the Tibial-Tissue thickness. A line was drawn from the lateral process of the talus to the head/neck junction of the talus (Yellow Line), and the distance of the parallel segment, extending from the head/neck junction of the talus to the end of the soft tissue shadow, was measured to determine the Talus-Tissue thickness.